Confronting Bolivia’s "Lack of Demographic Capacity": Protonatalism in Post-Revolutionary Bolivia, 1950s-1970s - Pacino, Nicole (Anuario de Historia de América Latina, 2023)
After coming to power in April 1952, the Movimiento Nacionalista Revolucionario (MNR) looked to address Bolivia’s economic problems, in part, through initiatives encouraging population growth. A 1953 report highlighted underpopulation as a cause of Bolivia’s limited economic potential. The solution to Bolivia’s “lack of demographic capacity” was public health measures that would lower morbidity and mortality rates and encourage reproduction to boost the country’s human capital. This article analyzes prevalent pronatalist tendencies in the MNR government, including positive eugenics and criticism of birth control, to demonstrate the centrality of population growth to the MNR’s political and economic agenda. At a time when other Latin American countries began implementing population control measures as a pathway to economic growth and political stability, as recommended by the United States and international organizations, Bolivia diverged from global discourses about overpopulation and embraced pronatalism. While the MNR welcomed some global development ideologies associated with modernization, they rejected population control and reframed population debates towards population growth and demographic reorganization. They married pronatalism with a modernizing agenda and revolutionary nationalism, demonstrating that MNR policies were fundamentally conservative on matters of reproduction and gender roles.